Reshaping forest management in Australia to provide nature-based solutions to global challenges. Issue 2 (3rd April 2021) - Jackson, W.; Freeman, M.; Freeman, B.; Parry-Husbands, H.
ABSTRACT: It is time to move beyond the era of conflict and develop a new shared vision for the management of Australia's public forests. We need more holistic approaches that encompass all forest values across the landscape, rather than the current approach of dividing public forest management up across different government agencies. More collaborative approaches will be required to galvanise the resources, skills and knowledge that enables this shift in shared governance. Recent bushfires in Australia have heightened concerns that the management of public forest lands has largely failed to ensure the health of forest ecosystems, build resilience, and secure a promised balance between economic, social and environmental values. Investment in efforts to adapt forest management to address climate change has been limited; and empowering and increasing the role of Indigenous Australians in forest management could be significantly improved. Furthermore, the COVID-19 pandemic has highlighted the need to improve the resilience of regional communities to major shocks and stresses caused by factors that encompass market dynamics, supply-chain disruptions and natural disasters. Three key strategies are proposed to strengthen forest management in Australia: first, establishing new shared governance models that bring together government agencies with Indigenous Australians and actors from the private sector and civil society; second, extending active and adaptive management across forest landscapes that builds resilience in our forests, local communities and society; and third, integrating traditional knowledge with scientific evidence and innovative technologies to enhance forest management for improved resilience and other outcomes.